... and six hundred thousand men were dead - Herschel I. Grossman (Brown University, Department of Economics, 2003)
The dispute that resulted in the secession of eleven Southern states from the Union and the ensuing Civil War proximately concerned the geographical expansion of slavery, but ultimately bore on the existence of the institution of slavery itself. This paper asks why in 1861 after seventy years of artful compromises over slavery Northern and Southern interests were not able to avoid secession and war. The paper seeks an answer that goes beyond a description of the breakdown of compromises based on existing constitutional arrangements. Instead the paper focuses on the failure of attempts to negotiate a new compromise. Combining theoretical and historical analysis the paper suggests that the increasing importance of the dispute over slavery for both Northern and Southern interests in the years leading up to 1861 was the critical development that led to war. The analysis also formalizes the role of overoptimism about the prospects for a quick and cheap victory as a contributing cause of the war. – Slavery ; Constitution ; Compromise ; Secession ; Armed Confrontation ; Civil War
Keywords: D74; 330; Bürgerkrieg; Sklaverei; Public Choice; Geschichte; USA